PENGARUH BERBAGAI JENIS MULSA TERHADAP PERTUMBUHAN AWAL TANAMAN MANGGA (Mangifera indica L.) - Ramli Ramli (Universitas Tadulako, 2009)
This research aim was to study the influence of various mulch types on early growth of mango crop grown in The Akademik Garden of Agricultural Faculty of Tadulako University, Palu. The experimental design was a Randomized Block Design with four replicates. The treatments were black plastic, white plastic, paddy straw, Seage grass Hay, paddy husk, and sawdust. Results of the research indicated that the mulch had significant effect on leaf number and length. The largest number and length of leaves was found in the paddy straw treatment which were 70 leave and 90.40 cm, respectively.